2013
DOI: 10.1038/srep03292
|View full text |Cite
|
Sign up to set email alerts
|

Braess's Paradox in Epidemic Game: Better Condition Results in Less Payoff

Abstract: Facing the threats of infectious diseases, we take various actions to protect ourselves, but few studies considered an evolving system with competing strategies. In view of that, we propose an evolutionary epidemic model coupled with human behaviors, where individuals have three strategies: vaccination, self-protection and laissez faire, and could adjust their strategies according to their neighbors' strategies and payoffs at the beginning of each new season of epidemic spreading. We found a counter-intuitive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 44 publications
(79 reference statements)
2
75
1
Order By: Relevance
“…Here, C R denotes the cost of infection to a partially resistant (immune) agent, while o k (α k ) is the perceived probability of becoming infected if vaccinated (non-vaccinated). Thus, different from respective expressions of discrete strategies [433,525,547], the second term in the right hand side of Eq. 231 is the perceived payoff of vaccination selection, and the third accounts for the perceived payoff of non-vaccinated behavior.…”
Section: How Does Feedback Influence Well-known Passive and Pro-activmentioning
confidence: 92%
See 2 more Smart Citations
“…Here, C R denotes the cost of infection to a partially resistant (immune) agent, while o k (α k ) is the perceived probability of becoming infected if vaccinated (non-vaccinated). Thus, different from respective expressions of discrete strategies [433,525,547], the second term in the right hand side of Eq. 231 is the perceived payoff of vaccination selection, and the third accounts for the perceived payoff of non-vaccinated behavior.…”
Section: How Does Feedback Influence Well-known Passive and Pro-activmentioning
confidence: 92%
“…The superscripts H and I denote healthy and infected states, while w is the probability of a susceptible to become infected. For more details, please refer to [547].…”
Section: Multiple-strategy Dilemma Framework: a Counter-intuitive Obsmentioning
confidence: 99%
See 1 more Smart Citation
“…[87] is that we might never guess what would happen by just looking at the decision-making rules alone, in particular when our choices will influence, and be influenced by, the choice of other people. Another good example can be found in a recent work [89], in which Zhang et al proposed an evolutionary epidemic game where individuals can choose their strategies as vaccination, self-protection or laissez faire, towards infectious diseases and adjust their strategies according to their neighbors' strategies and payoffs. The "disease-behavior" coupling dynamical process is similar to the one implemented by Ref.…”
Section: Dynamics On Lattices and Static Networkmentioning
confidence: 99%
“…Bauch and Earn [4] investigated the impacts of vaccination policy on the level of vaccination coverage and found that voluntary vaccination was unlikely to reach the group-optimal level. Zhang et al [37] studied the epidemic spreading with voluntary vaccination strategy on both Erdos-Renyi random graphs and Barabasi-Albert scale-free networks and Zhang et al [36] investigated effects of behavioral response and vaccination policy on epidemic spreading. The transmission dynamics of measles epidemics have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%